Longitudinal evaluation of homoeopathic treatment for psoriasis using the PASI scale: Insights from a case study approach - Dr. Amit Nayak; Dr. Heena Rawal; Dr. Poorav Desai; Dr. Bhoomi Varma (The Bioscan, 2025)
Psoriasis is a chronic immune-mediated inflammatory skin disease affecting approximately 2-3% of the world’s population. This study describes the long-term homoeopathic treatment over 18 months of a 34-year-old female patient diagnosed with psoriasis. The patient presented with extensive skin lesions including scaling, redness, and itching, primarily affecting the legs, with an initial Psoriasis Area Severity Index (PASI) score of 14.4. Individual homoeopathic remedies including Sulphur, Calcarea Carbonica, and Ferrum Phosphoricum were prescribed based on the patient’s symptoms and treatment response. The treatment resulted in significant improvement, with the final PASI score reducing to 2.4, representing an 83.33% improvement. Symptoms such as scaling, redness, and itching intensity decreased. The study demonstrates the potential effectiveness of individualized homoeopathic treatment in managing chronic psoriasis, as evidenced by objective PASI score improvement and sustained clinical response. KEYWORDS Psoriasis, Homoeopathy, PASI Score, Chronic Skin Disease, Scaly Patches, Individualized Treatment.